An updated checklist of inland Cladocera (Crustacea: Orders Ctenopoda and Anomopoda) from Venezuela - de Roa, Evelyn Zoppi; López, Carlos (Zootaxa, 2008)
An updated checklist of cladoceran orders Ctenopoda and Anomopoda from inland aquatic habitats in Venezuela is provided, containing a total of 112 species grouped into 39 genera. Recorded cladoceran species of Venezuela represent 30% of the world’s described 370 species of Ctenopoda and Anomopoda. The most representative genera are Alona, Diaphanosoma, Moina, Macrothrix, and Chydorus with 19, 10, 7, 6, and 5 species, respectively. Most records (45%) are Neotropical and about 4% are endemic species. Some aspects related to geographical distribution and species richness in the Venezuelan hydrographic basins are briefly discussed.